NYANTRIK LEARNING MODEL IN THE FIELD EXPERIENCE PRACTICE PROGRAM FOR THE BACHELOR (S-1) WORKFORCE EDUCATION INSTITUTIONS - haryono, Haryono (Dewantara, 2014)
Objective: The objectives of this research are to develop Nyantrik learning model in the Field Experience Practice Program for the bachelor (S-1) Workforce EducationInstitutions, and to investigate the effectiveness of the Nyantrik learning model.Method: This research was conducted at Teacher Training Institutions in the regions of Ngawi Residency, East Java, Indonesia. It used the research & development method with the following phases: preliminary studies (library research, field survey, product drafting), development (limited experiment and field experiment), and testing (pre-test, treatment, and post-test).Result: The results of the research are as follows: 1) Nyantrik learning model is a learning model which is used in the Field Experience Practice Program for the bachelor (S-1) students of the Teacher Training Institutions with the process of teacher competency transformation through imitation, identification, and internalization of the competencies owned by the mentor teachers. The teacher competency transformation is done by applying the teaching proposed by Ki Hajar Dewantara that is tut wuri handayani (supporting from the back), ing madya mangun karsa (building spirit in the middle), and ing ngarsa sung tulada (setting an example in the front) in formal and informal Nyantrik situations. 2) The results of the learning model effectiveness test are as follows: a) The teacher competency transformation through imitation, identification, and internalization can take place well; b) the application of the teaching of Ing ngarsa sung tuladha, ing madya mangun karsa, and tut wuri handayani can form the teacher competencies maximally; and c) the blend between the formal Nyantrik and the informal Nyantrik can create a harmonious mentoring from the mentor teachers to the students doing the Field Experience Practice Program including the implementation of periodical workshops, which can form the teacher competencies maximally, namely: their pedagogical, professional, personal, and social competencies. d) Nyantrik Learning Model is better and more effective than the Apprenticeship Learning Model.Conclusion: Based on the results of the research, a conclusion is drawn that the Nyantrik learning model is very effective to be applied in the Field Experience Practice Program as to form the teacher competencies of the bachelor (S-1) Workforce Education Institutions.